1988
DOI: 10.1007/bf00396334
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of cytokinins in Craigella tomato and a sideshootless mutant

Abstract: Post-embedding immunocytochemical techniques using peroxidase-antiperoxidase or immunoglobulin G-gold as markers were used for the localization of cytokinins (CKs) in two isogenic lines, Craigella (C) and Craigella lateral suppressor (Cls), of tomato Lycopersicon esculentum Mill. Terminal buds, nodes, hypocotyl segments and root tips were submitted to a periodate-borohydride procedure, to obtain the coupling of isopentenyladeosine and zeatin riboside to cellular proteins, followed by a fixative step with a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 35 publications
1
28
1
Order By: Relevance
“…Because cytokinins are synthesized in root tips and are at relatively high concentrations in roots (Sossountov et al, 1988;Chiappetta et al, 2001), we can speculate that a mechanism exists to reduce the sensitivity of cells at the root tip to cytokinins to suppress their growth-inhibitory effects. This system may involve the gene STUNTED PLANT1 (Baskin et al, 1995), and PLS also may encode a component of this mechanism.…”
Section: Pls Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because cytokinins are synthesized in root tips and are at relatively high concentrations in roots (Sossountov et al, 1988;Chiappetta et al, 2001), we can speculate that a mechanism exists to reduce the sensitivity of cells at the root tip to cytokinins to suppress their growth-inhibitory effects. This system may involve the gene STUNTED PLANT1 (Baskin et al, 1995), and PLS also may encode a component of this mechanism.…”
Section: Pls Functionmentioning
confidence: 99%
“…For example, cytokinins can act as important regulators of cell division and appear to be synthesized in root tips, although exogenous cytokinins can inhibit root growth (Sossountov et al, 1988;Riou-Khamlichi et al, 1999;Chiappetta et al, 2001). Cytokinins can act antagonistically with auxin in some developmental contexts, such as in lateral root development, but they also can act synergistically, as in ethylene biosynthesis (Vogel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…They are synthesised in root tips (Chiappetta et al, 2001;Sossountov et al, 1988), and might be expected to limit the level of EXO expression in the meristem, since Northern analysis showed downregulation of EXO transcription by cytokinins. Therefore, EXO expression may be antagonistically upregulated by auxin and downregulated by cytokinin in the meristem, to modulate its level of expression.…”
Section: Regulation By Hormonesmentioning
confidence: 99%
“…The relative distribution of Z + ZR per bud also showed a steep downward gradient as for IAA. We have recently shown (18) by immunocytochemical methods that tomato inhibited buds are well correlated with very low contents of endogenous CKs in their quiescent meristematic cells, and we concluded that CKs are necessary for axillary bud growth. Thus, as for IAA, the distribution of Z-type CKs within the buds fits well with growth activity: actively growing buds contained the highest levels of these hormones.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, it seems important to analyze the subcellular localization of the hormone. This important question can be answered by the use of immunocytochemical methods to localize plant hormones as initiated in our laboratory (17)(18)(19) to delineate the possible role of a regulator not based on its tissue or organ concentration.…”
Section: Discussionmentioning
confidence: 99%